Principal leadership and teacher professional learning in Turkish schools: examining the mediating effects of collective teacher efficacy and teacher trust - Karacabey, Mehmet Fatih (Routledge Journals, Taylor & Francis Ltd, 2022)
The present study sought to contribute to the growing international knowledge base regarding the influence of school leadership on teacher learning by examining the relationship between principals' instructional and transformational leadership types and teachers' professional learning perceptions with the mediating effects of teachers' perceptions of collective efficacy and trust. A cross-sectional survey design of the quantitative research method was employed using the data collected from a total number of 1,200 teachers in Turkey. Mediation analysis in structural equation modelling (SEM) with the bootstrapping method was used to analyse the structural relations among variables. The result showed that both principals' instructional and transformational leadership types were significantly related to teacher professional learning, mediating by teacher trust and collective teacher efficacy. The study reconfirmed the results of the growing body of global literature on the relationship between principal leadership and teacher professional learning and practice.